Risk management practices of islamic financial institutions in Malaysia and Pakistan / Rashidah Abdul Rahman … [et al.] - Abdul Rahman, Rashidah; Omar, Normah; Tafri, Fauziah Hanim; Masood, Omar (Research Management Institute (RMI), 2012)
The focus of this study is to examine the effectiveness of the risk management process (understanding risk management, risk identification, risk assessment and analysis, and risk monitoring) on risk management practices among Islamic banks in Malaysia and Pakistan. The study also compares the risk management process and practices between the banks in both countries. The study found that Islamic banks in Malaysia and Pakistan are somewhat efficient in managing risk and that there is a significant difference between the banks in Malaysia and Pakistan in the practice of understanding risk management and risk identification. The results also indicate that risk identification and risk assessment and analysis are the most influencing factors in risk management practices in both countries.